Ferramentas web para construção de uma biblioteca pública digital livre - Andrade, Robéria de Lourdes de Vasconcelos (2014)
Once the noteworthy role of public libraries as institutions in the development process is recognized, the current piece of research had as general objective the analysis of free tools for the development of digital libraries describing thus their use. The research development was divided into four phases. The first one, named preparation, intended to identify the elements used by digital libraries which are accessible by means of web, following a set of criteria, characterized by the sample that was composed of eighteen libraries in the Portuguese language. In this phase, a quantitative/qualitative methodological approach was used. Data collection was carried out through techniques such as content analysis, documental analysis and questionnaire use so as to validate the mentioned analysis. In relation to the second phase, named planning, the choice of the technological elements available for the implementation of a digital library was fulfilled. For data collection, the documental analysis was used. The third one, the development, was composed of activities concerning a prototype development of a public digital library as well as the description of its construction procedures. Finally, in the fourth phase, the control, the use and the users´ impression of the developed library were measured and analyzed. For data collection, the webometric analysis and the on-line questionnaire answered by the users were employed. As the research was developed, it was verified that there is no standard model for digital libraries that are in their operational process, different from the traditional ones, being highlighted that there is disparity in the observed characteristics. In regard to archive policy, the research realized that the digital libraries do not have it or they are not documented. The lack of the professional librarian, in these information units, was also emphasized. With reference to the tools, the available diversity in the web allows any traditional library, with the suitable skilled human resources, to be part of the technological world without great difficulties. The metrics employed to measure the prototype use perceived numbers that allow identifying the users´ access and satisfaction. As final result, this research indicates alternatives for the librarians and managers of information units demonstrating thus procedures that enable free access to quality and democratic information, without burdening the institution´s budget.